Новые виды микроспоридий кровососущих комаров северных областей Украины - Килочицкий, П.Я. (Вестник зоологии, 1998)
С использованием методов световой и электронной микроскопии диагностировано 6 видов микроспоридий из комаров родов Anopheles and Aedes. Six species of microsporidia from Parathelohania and Amblyospora genera have been detcctcd amond 7 species of blood sucking mosquitoes from Anopheles and Aedes genera with the use of light and electrone microscopcs. Three spccies, namely P. detinovcic from the A. maculipennis, P. issiae from the A. claviger and A. theophanica from the A. annulipes are new for science. Mononuclear spores of P. detinovac sp. n. 5,0-6,0 x 3,2-3,6 mkm (fresh), lamellar polaroplast; anisophillar polar tube with 6-8 coins, 2 of them belongs to basal section. Mononuclear spores of P. issiae sp.n. 4,8—5,0 x 2,8—3,8 mkm (fresh); lamellar polaroplast; anisophillar polar tube with 5 (5—6) coins, 3 (2—3) of them belonging to basal part. Mononuclear spores of A. theophanica sp. n.: 6,0—6,8 x 4,4—5,0 mkm (fresh), formed by 8. Sporophorous vesicles containing tubular and lamellar mathabolic granules. Mucocalyx absent. Exospore thiner then endospore. Polaroplast lamellar. Anisophillar polar tube with 8 (7,5—8) coins, 4 of them belonging to basal section. Microsporidian A. cxcruci from the A. c.cinereus, A. puctor from the A. punctor and A. c.cinereus, A. inimica from the A. c.caspius are new for the territory of Ukraine.